Premature Infants: A Care and Post-Discharge Follow-Up Model - Hayeese, Wanisa; Chaimongkol, Nujjaree; Damklia, Wimolwan; Mama, Thida; Kholoarsae, Yaowaree; Pengmak, Thaweeporn; Thepso, Sukanya (Princess of Naradhiwas University Journal, 2019)
The objective of this participatory action research was to develop a care and follow-up model for premature infants after discharge from hospitals. Purposive sampling was used to form 2 groups: a sample group to develop the care and follow-up model for premature infants after discharge from hospitals had 20 participants. And the sample group of 15 participants received the care and post-discharge follow-up model for premature infant, which were divided into three phases: preparation, implementation and evaluation. Qualitative data were collected by means of interviews, observation, focus group discussion, and writing field notes. Data were analyzed by using content analysis for the qualitative approach. Descriptive statistics were used for demographic information and the participants’ satisfaction of the model. The results revealed that this model offered: 1) a structural model for several stakeholders to continue giving care from hospitals in NICU until discharged home and infant’s age of 12 months (Newborn Home Health care: NHHC), 2) a transitional record form for discharge planning of the premature infants (NHHC-1), 3) a transitional record form for follow-up mothers and their premature infant after birth (NHHC- 2), and 4) a complimentary manual of care for premature infants after discharge from hospital. Satisfaction towards the research procedures among the group of participants in the model development was at a high level (M = 3.38, SD=0.33 และ M = 3.63, SD=0.23, respectively). These findings indicate that this care and post- discharge follow-up model for premature infants could lead to reach achievement in better quality of care for premature infants